Analysis of Antibacterial and Antiviral Properties of ZnO and Cu Coatings Deposited by Magnetron Sputtering: Evaluation of Cell Viability and ROS Production - Vibornijs, Viktors; Zubkins, Martins; Strods, Edvards; Rudevica, Zhanna; Korotkaja, Ksenija; Ogurcovs, Andrejs; Kundzins, Karlis; Purans, Juris; Zajakina, Anna (MDPI, 2024)
The development and testing of antimicrobial coatings continues to be a crucial approach, considering the ongoing emergence of antibiotic-resistant bacteria and the rapid transmission of highly pathogenic viruses. In this study, three types of coatings—pure metallic copper (Cu), zinc oxide (ZnO), and a three-layer zinc oxide and copper mixed coating (ZnO/Cu/ZnO)—were deposited by magnetron sputtering on polyethylene terephthalate substrates to evaluate their antimicrobial potential using various microorganisms, including viruses. Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria were used for the assessment of antibacterial properties. Antiviral testing was performed using MS2 bacteriophage and replication-deficient Semliki Forest virus, both representing single-stranded RNA-containing viruses. The samples’ ability to cause reactive oxygen species formation was measured, and the effect on bacterial metabolic activity was evaluated. Cu-coated samples showed high inhibitory activity (>95%) against E. coli and S. aureus bacteria, as well as against tested viruses (SFV and MS2). The antibacterial and antiviral properties of ZnO/Cu/ZnO and ZnO coatings were not significant. Although ZnO/Cu/ZnO and ZnO caused inhibition of the metabolic activity of the bacteria, it was insufficient for complete bacteria eradication. Furthermore, significant reactive oxygen species (ROS) production was detected only for single Cu-coated samples, correlating with the strong bacteria-killing ability. We suppose that the ZnO layer exhibited a low release of Zn ions and prevented contact of the Cu layer with bacteria and viruses in the ZnO/Cu/ZnO coating. We conclude that current ZnO and Cu-ZnO-layered coatings do not possess antibacterial and antiviral activity. © 2023 by the authors. --//-- This is an open access article Analysis of Antibacterial and Antiviral Properties of ZnO and Cu Coatings Deposited by Magnetron Sputtering: Evaluation of Cell Viability and ROS Production.Vibornijs, V.; Zubkins, M.; Strods, E.; Rudevica, Z.; Korotkaja, K.; Ogurcovs, A.; Kundzins, K.; Purans, J.; Zajakina, A.; Coatings 2024, 14, 1, 14. DOI 10.3390/coatings14010014, published under the CC BY 4.0 licence.
The authors thank Andris Dislers for providing the MS2 bacteriophage and for the establishment of a plaque assay methodology. The Institute of Solid-State Physics, University of Latvia, as a Center of Excellence, is thankful to the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART for provided equipment: Helios 5 UX dual-beam scanning electron microscope, RC2 spectroscopic ellipsometer, and Cary7000 spectrophotometer. 2
Keywords: Research Subject Categories::NATURAL SCIENCES; antibacterial activity; antiviral activity; bacterial cell viability; copper coatings; reactive oxygen species; zinc oxide coatings